Financial Inclusion, and the Role of the Non-Bank Financial Industry in the Development of Micro, Small and Medium Enterprises - Herispon, Herispon (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
Financial inclusion is a must to be implemented, which is considered to reduce the gap and poverty that occurs in the community through financial services and banking with the motor of the banking industry (IP) and the non-bank financial industry (IKNB) including BUMD, BUMD with the object of business sector micro and small or UMKM. IKNB includes competent authorities in the development of the micro and small-medium enterprises sector through continuous capital assistance, coaching and supervision. The concept and model offered in this paper is a national movement of foster parents who can be applied in the sector of micro and small medium enterprises referred to as GN-OTA UMKM. These concepts and models seem simple and obsolete, if this model has never been implemented for the development of UMKM then this model becomes a new model and IKNB can be a pioneer or a major player in the development of UMKM